Republic of Guinea : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
The 2003 Guinea Country Financial Accountability Assessment (CFAA) was implemented jointly with the 2003 Guinea Public Expenditure Review (PER), and both analysis will be reported as the Integrated Public Expenditure Review and Fiduciary Assessment (PER-FA) for Guinea. This approach has been followed in order a) to have a cohesive, and coherent set of analysis, and recommendations on Public Finance, b) to reduce the demands on the Government of Guinea, which might have resulted from a duplication of reviews being carried out in the same time frame. This approach reduces the potential overlap in the scope of PER and CFAA. This stand alone CFAA report is based on the chapter on Public Financial Management systems and processes in the PER-FA, with some additional context added. The quality of Public Financial Management in Guinea, does not yet provide sufficient assurance for external donors to implement their projects through the government's own systems via, for example, direct budgetary support. In some aspects of public financial management, e.g. the formal commitment control system, Guinea's simple and pragmatic approach is more effective than some of the more sophisticated, and expensive systems in the sub region. However, the level of public expenditures processed outside the central commitment control system, in particular by means of payment orders and advances remains a concern. Corruption in public service remains a concern, although there are encouraging signs from the activities of the anti-corruption Commission. Recent changes, in particular high-level responsibilities, have eased some perceived roadblocks to the follow through of anti-corruption activities. Nevertheless, Guinea has made substantial progress in getting up to date in its statutory financial reporting. During the 1990's there had been a significant lag in the statutory financial reporting obligations (la Loi de reglement). As at March 2003, with the approval of such law, Guinea was fully up to date with the legal requirements. In order to improve accountability, there is a need to continue to improve the quality, timeliness and availability of financial information on budgets, expenditures, and revenues. Measures should include : Establishing a program to report actual vs budgeted expenditures at the decentralized community level for education, health, and rural services, together with a requirement for regular accountability; Implementing a policy of moving the management of budgeted expenditures to the closest point at which services can be delivered cost effectively; Simplifying the expenditure control processes at the decentralized level; and, Developing a more predictable flow of funds to the decentralized level. And, to sustain the decentralization process there is need to: Support the development of fiduciary capacity at the decentralized level, by providing the necessary personnel, training, and technical guidance; Provide the basic equipment, infrastructure and tools to support decentralized units; Progressively establish computer terminals for the commitment control system closer to the decentralized level.